(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Physical anthropology is an interdisciplinary science which in everyday practice applies all the knowledge that medical sciences, have accepted as reliable and scientifically solid facts or processes, and qualitative and quantitative definitions with the help of which accurate and reliable statements can be made. The humerus itself is a complex anatomic unit so anthropometric study was devised on the same.